2002
DOI: 10.1073/pnas.202049999
|View full text |Cite
|
Sign up to set email alerts
|

Activity patterns in human motion-sensitive areas depend on the interpretation of global motion

Abstract: Numerous imaging studies have contributed to the localization of motion-sensitive areas in the human brain. It is, however, still unclear how these areas contribute to global motion perception. Here, we investigate with functional MRI whether the motionsensitive area hMT ؉ ͞V5 is involved in perceptual segmentation and integration of motion signals. Stimuli were overlapping moving gratings that can be perceived either as two independently moving, transparent surfaces or as a single surface moving in an interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
48
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(62 citation statements)
references
References 48 publications
13
48
0
Order By: Relevance
“…The change in the activation in the occipito-temporal motion-sensitive area in conjunction with the perception of global motion is also reported in the previous fMRI studies [11,12], and the intra-parietal region were reported to be activated during the mental imagery processing [13,14], which suggests that the perception of moving 3D object from 2D random-dot motion includes both perception of global motion and 3D mental image processing, that are accomplished by the cooperative activation in the ventral and dorsal visual pathways.…”
Section: Discussionsupporting
confidence: 74%
“…The change in the activation in the occipito-temporal motion-sensitive area in conjunction with the perception of global motion is also reported in the previous fMRI studies [11,12], and the intra-parietal region were reported to be activated during the mental imagery processing [13,14], which suggests that the perception of moving 3D object from 2D random-dot motion includes both perception of global motion and 3D mental image processing, that are accomplished by the cooperative activation in the ventral and dorsal visual pathways.…”
Section: Discussionsupporting
confidence: 74%
“…There is ample evidence to suggest that perceived changes in motion direction, no matter whether they are spontaneous or stimulus-driven, are reflected by eventrelated hMTϩ/V5 activations (16,(23)(24)(25)(26)(27)(28). We hypothesized that if the inferior frontal cortex was causally involved in inducing switches during bistable perception, then frontal activations in association with spontaneous perceptual switches should precede those in hMTϩ/V5.…”
Section: Resultsmentioning
confidence: 95%
“…According to evidence from neurophysiological studies in nonhuman primates (30,31) and human fMRI studies (32), subjective fluctuations in perception are reflected by relative activity levels of neuronal populations representing either perceptual content. The finding of switch-related hMTϩ/V5 activations in bistable motion perception (16,(24)(25)(26)28) has led to the suggestion that separate direction-selective neuronal populations coding for different directions of motion might be in rivalry and that, at perceptual switches, one of these populations displays a transient rise in activity. This interpretation is supported by the electrophysiological observation in monkeys that responses of directionally selective cells in MT signal the perceived direction of motion in ambiguous motion stimuli (27).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of direction repulsion, a number of authors have proposed that the mechanism driving it occurs at the early local motion-processing stages (Marshak & Sekuler 1979;Hiris & Blake 1996;Grunewald 2004;Wiese & Wenderoth 2007), while others have proposed it occurs at the later global motion processing stages ( Wilson & Kim 1994;Kim & Wilson 1996, 1997Benton & Curran 2003). These two stages of motion processing have been identified as occurring in area V1 and the human homologue of macaque MT/V5, respectively (Snowden 1994;Castelo-Branco et al 2002;Huk & Heeger 2002). Again, in the case of the DAE, there is evidence supporting both a local (Kohn & Movshon 2004;Curran et al 2006a) and global motion processing (Kohn & Movshon 2004;Wiese & Wenderoth 2007) account.…”
Section: Introductionmentioning
confidence: 99%